Upaya Dukungan Keluarga Terhadap Pencegahan Covid-19 - Aida Kubangun, Nur; Nawangwulan, Kurniati; Kurniawati, Kurniawati; Rena Pudyastuti, Rita; Fahri, Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
The tragedy of the mysterious emergence of the coronavirus continues in several countries in the world. The spread of the covid 19 virus has become an outbreak that is very troubling for the community to causes respiratory infections. The implementation of health education with efforts to involve family and community support for covid-19 prevention aims to improve the ability of the community to apply hand washing with soap using running water or hand sanitizer. Proper hand washing techniques are one of the measures in preventing the risk of covid-19 disease, as well as improving the community's healthy lifestyle, which is emphasized in the smallest unit in the community, namely the family. The method carried out in preventing covid-19 disease is community service in the form of counseling, demonstrations, and role play. The results of community service in an effort to increase family support for the prevention of covid-19 disease can be absorbed and accepted by families and communities with the psychomotor ability to demonstrate hand washing up to 80% of participants can repeat how to wash their hands properly and correctly. This service activity can be improved by the puskesmas with family and community support.